The Practice of Paneta Mawinne in The Sumbanese Tribe of East Nusa Tenggara Perspective of Islamic Law - Muthoifin; Al-Gifari; Afiyah, Ishmah; Geraldine, Edwards; Affandi, Muchammad Taufiq (NAJAHA, 2024)
This research aims to explore the phenomenon of forced marriage, particularly the practice of Paneta Mawinne or arrest marriage, among the Sumba tribe in East Nusa Tenggara, Indonesia. The study specifically examines this practice through the lens of Islamic law, analyzing whether such cultural customs align with or contradict Islamic legal principles. The research adopts a qualitative approach using secondary data collected through literature reviews from credible sources. Data were gathered over several months from academic journal articles, online news outlets, and social media platforms, including relevant videos that document the practice. The analysis focuses on Islamic jurisprudence regarding marriage, which emphasizes mutual consent, justice, and the absence of coercion. Findings indicate that Paneta Mawinne involves significant elements of force and lack of consent, especially on the part of the bride, which is fundamentally incompatible with the principles upheld in Islamic law. Islamic teachings require the voluntary agreement of both parties in a marriage contract, making any form of coercion a violation of Sharia. The originality of this study lies in its intersectional analysis, combining anthropological insights with Islamic legal evaluation to assess a localized cultural practice. By highlighting the contradiction between local customs and Islamic values, this research contributes to broader discussions on cultural relativism, religious norms, and human rights. Ultimately, it calls for greater awareness and legal clarity to ensure that traditional practices do not undermine individual autonomy and religious ethics in Muslim communities.